Analisis Strategi Pengembangan UMKM Kabupaten Sidoarjo di Masa Pandemi Covid-19 - Rannu Dyah Rahmadani; Waspodo Tjipto Subroto (Universitas Negeri Surabaya, 2022)
Micro, Small and Medium Enterprises (MSMEs) are the sector that absorbs the largest workforce in Indonesia up to 97% and is the most important part of the country's economy. When Indonesia experienced the monetary crisis in 1998, MSMEs were able to restore the Indonesian economy. However, due to the Covid-19 pandemic that is currently hitting Indonesia, it causes a decline in production for MSMEs in Sidoarjo Regency and contributes to the country's weak economy. This study aims to analyze and identify the factors that cause the decline in the existence of MSMEs in Sidoarjo Regency using SWOT analysis and analysis of internal and external factors, as well as strategies for developing MSMEs in Sidoarjo Regency. This study uses the Systematic Literature Review (SLR) method, which uses literature in the form of journals, papers, or seminar proceedings, and reports from government or private institutions, as a reference in data collection. The results of the research are in the form of development strategies according to the needs of MSMEs in Sidoarjo Regency. This study provides a contribution to the application of strategic development related to the determination (formulation) of strategy in MSMEs which are the driving force of the largest economic sector